2018
DOI: 10.1111/nep.13472
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the role and mechanism of Wnt/β‐catenin signalling in kidney fibrosis

Abstract: Wnt/β‐catenin is an evolutionarily conserved, developmental signalling pathway that regulates embryogenesis, injury repair and pathogenesis of human diseases. Dysregulated activation of Wnt/β‐catenin is associated with the development and progression of renal fibrotic lesions after injury. Wnt are induced and β‐catenin is activated in various models of experimental chronic kidney disease (CKD) and in human nephropathies. Recent findings indicate that pro(renin) receptor is an amplifier of Wnt/β‐catenin by acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 50 publications
1
54
0
5
Order By: Relevance
“…Upon the binding of Wnt ligands to the receptors frizzled (Fzd) and lipoprotein receptor–related protein (LRP) 5/6, GSK3β activity is repressed, and then, β‐catenin would be released and activated to trigger cell injury and renal fibrosis. Although β‐catenin could be up‐regulated in multiple cells such as podocytes, interstitial fibroblasts, endothelial cells and inflammatory cells, it is predominantly localized in renal tubular cells in injured kidneys . These observations suggest the potential relationship between CXCR4 and β‐catenin in renal tubular cell injury and fibrosis.…”
Section: Introductionmentioning
confidence: 94%
“…Upon the binding of Wnt ligands to the receptors frizzled (Fzd) and lipoprotein receptor–related protein (LRP) 5/6, GSK3β activity is repressed, and then, β‐catenin would be released and activated to trigger cell injury and renal fibrosis. Although β‐catenin could be up‐regulated in multiple cells such as podocytes, interstitial fibroblasts, endothelial cells and inflammatory cells, it is predominantly localized in renal tubular cells in injured kidneys . These observations suggest the potential relationship between CXCR4 and β‐catenin in renal tubular cell injury and fibrosis.…”
Section: Introductionmentioning
confidence: 94%
“…Studies by our and others have shown that activation of STAT3 and β‐catenin contributes to renal fibrogenesis 30‐32 . We hypothesized that HDAC8 may also regulate activation of these two signaling pathways.…”
Section: Resultsmentioning
confidence: 93%
“…Of course, targeting only the TGF-β signaling pathway is insu cient to reduce renal brosis. Some studies indicated that CTGF, Wnt/β-catenin, renin-angiotensin system, oxidative stress, and so forth, were implicated in renal brosis [16,30,31]. Wnt/β-catenin is an evolutionarily conserved signaling pathway involved in the regulation of tissue homeostasis, organ development, and injury repair [32].…”
Section: Discussionmentioning
confidence: 99%
“…4c, d, i). Wnt/β-catenin elicited renal brosis by inducing multiple brogenic genes such as RAS components, matrix metalloproteinase-7 (MMP-7), plasminogen activator inhibitor 1 (PAI-1), and Snail1 [31]. Zhou et al described Wnt/β-catenin as the major upstream regulator, which controls the expression of all tested RAS components in the kidneys [38].…”
Section: Discussionmentioning
confidence: 99%